2004
DOI: 10.1111/j.1939-165x.2004.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical study of Ki‐67 as a prognostic marker in canine mammary neoplasia

Abstract: The prognostic value of the Ki-67 index in canine mammary tumors by using wet-fixed cytology imprint specimens was similar to that observed previously for histologic specimens. Immunocytochemical detection of Ki-67 could improve the accuracy and value of cytology by providing safe and rapid information about malignancy and patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
3
29
1
5
Order By: Relevance
“…This result confirms literature data reporting Ki-67 as a marker for carcinomas and a marker of unfavorable prognosis (Zuccari et al 2004). PCNA increases after the G1 phase of the cell cycle, reaching a maximum peak in the S phase and decreasing after G2, and then presents very low levels in the M phase and in quiescent cells which are not detected by immunohistochemical methods (Tsuji et al 1992, Huang et al 1994, Rabenhorst et al 1994, Martinez-Lara et al 1996.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This result confirms literature data reporting Ki-67 as a marker for carcinomas and a marker of unfavorable prognosis (Zuccari et al 2004). PCNA increases after the G1 phase of the cell cycle, reaching a maximum peak in the S phase and decreasing after G2, and then presents very low levels in the M phase and in quiescent cells which are not detected by immunohistochemical methods (Tsuji et al 1992, Huang et al 1994, Rabenhorst et al 1994, Martinez-Lara et al 1996.…”
Section: Discussionsupporting
confidence: 79%
“…More recently, other authors have tried to relate cell proliferation markers with the diagnosis, prognosis and outcome of breast neoplasms (Pena et al 1998, Zacchetti et al 2003, Kushlinskii et al 2004, Zuccari et al 2004, Nowak et al 2006. Nowak et al (2006) confirmed the relationship between Ki-67 and PCNA.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6]8,16 In veterinary medicine, Ki-67 expression has been described as a proliferation marker and of predictive value for survival of animals with tumors of several nonnervous tissues. [13][14][15][17][18][19][20][21][22][23] It has also been used as a proliferation marker in various intracranial neoplasms including meningiomas in dogs. 24-27,a Angiogenesis is the process leading to the formation of new vessels from a pre-existing vascular network, and is essential for the growth and invasion of neoplasms.…”
mentioning
confidence: 99%
“…For this reason, antibodies against Ki-67 are increasingly being used in human and veterinary oncology as prognostic markers in different types of neoplasms. MIB-1 is the monoclonal antibody developed against the antigen that can be used on routinely formalinfixed, paraffin-wax embedded tissues after microwave antigen retrieval (12 (67,73,94,115). However, one study dealing with Ki-67 immunolabelling in canine mammary tumours reported lack of prognostic significance of this marker (52).…”
Section: Ki-67mentioning
confidence: 99%